Growth and production of pakchoy (brassisca rapa l.) Due to the application of bioboost fertilizer and sugarcane bagasse compost - Aisyah Lubis; Iwan Hasrizart; Erlita Chaniago (Sean Institute, 2024)
This research aims uto knowgrowth and production of pak choy (brassisca rapa L.) plants due to the application of Bioboost fertilizer and bagasse compost. This research was carried out on community agricultural land. Asam Kumbang Village, Medan Selayang District. North Sumatra Province. This research was carried out in April 2023 to June 2023. This research used a Randomized Block Factorial Design with 2 factors studied and 3 replications where the first factor was Bioboost fertilizer (B), consisting of 4 levels, namely: B0 = 0 ml (not given Bioboost fertilizer), B1 = 10 ml/1 liter of water , B2 = 20 ml/1 liter of water, B3 = 30 ml/1 liter of water. The second factor is Sugarcane Bagasse Compost(T), consisting of4levels are:T0 = 0 Kg (without using bagasse compost), T1 = 0.5 kg/plot, T2 = 1 kg/plot, T3 = 1.5 kg/plot. The parameters observed were number of leaves, leaf width and plant weight per plot. The research results show that providing bioboost fertilizersignificantly different for leaf width parameters and pakchoy weight parameters per plot but not significantly different for leaf number parameters.Pemberiansugarcane bagasse compost and iInteraction of providing bagasse compost and bioboost fertilizerhas no significant effect on all parameters